English as a foreign language students’ mindfulness, academic motivation, and academic performance - Ismail Petrus; Lingga Agustina Suganda; Ayu Ulivia (Institute of Advanced Engineering and Science, 2022)
Previous studies found that academic motivation has a role in affecting academic performance. Along with that, the experts lately investigate mindfulness as one of the cognitive aspects related to student’s performance. This study aimed to find out the correlations among mindfulness, academic motivation, and academic performance in the context of English as a foreign language (EFL) student in Indonesia. Using a quantitative correlation design, this study involved 170 students from English education study program in a university in Indonesia. Five Facets Mindfulness Questionnaire (FFMQ), Academic Motivation Scale (AMS), and grade point average (GPA) official data were used as data collection instruments. Furthermore, to measure the correlation and contribution between the variables, Pearson product-moment correlation coefficient and regression analyses were conducted. The result of this study showed that most students had low mindfulness scale, high AMS with a dominant extrinsic motivation type, and very satisfactory GPA. However, there was no correlation among mindfulness, academic motivation, and academic performance. Moreover, it was found that only amotivation subscale has negative significant correlation with academic performance.